Speech Fluency Production and Perception in L1 (Slovak) and L2 (English) Read Speech - Mareková, Lucia; Beňuš, Štefan (Language and speech, 2025)
Research on fluency in native (L1) and non-native (L2) speech production and perception helps us understand how individual L1 speaking style might affect perceived L2 fluency and how this relationship might be reflected in L1 versus L2 oral assessment. While the relationship between production and perception of fluency in spontaneous speech has been studied, the information provided by reading has been overlooked. We argue that reading provides a direct and controlled way to assess language proficiency that might complement information gained from spontaneous speaking. This work analyzes the relationship between speech fluency production and perception in passages of L1 (Slovak) and L2 (English) read by 57 undergraduate Slovak students of English and rated for fluency by 15 English teachers who are Slovak natives. We compare acoustic production measures between L1 and L2 and analyze how their effect on perceived fluency differs for the two languages. Our main finding is that the articulation rate, the overall number of pauses, and the number of between-clause and mid-clause pauses predict ratings differently in L1 Slovak versus L2 English. The speech rate and durations of pauses predict ratings similarly in both languages. The contribution of our results to understanding fluency aspects of spontaneous and read speech, the relationship between L1 and L2, the relationship between production and perception, and to the teaching of L2 English are discussed.